Adenovirus E1B proteins are required for accumulation of late viral mRNA and for effects on cellular mRNA translation and transport. - Babiss, L E (1985)
Late in adenovirus infection, large amounts of viral mRNA accumulate while cell mRNA transport and translation decrease. Viruses deleted in the E1B region of type 5 adenovirus do not produce the same outcome: (i) viral mRNA synthesis by the mutants is normal, delivery to the cytoplasm is 50 to 75% of normal, but steady-state levels of viral mRNA are decreased 10-fold; (ii) cell mRNA synthesis and transport continue normally in the mutant virus-infected cell; and (iii) translation of preexisting cell mRNA which is disrupted in wild-type infection remains normal in mutant-virus-infected cells. Thus E1B proteins are required for accumulation of virus mRNA and for induction of the failure of host cell mRNA transport and translation. If a single function is involved, by inference the transport and some aspect of translation of mRNAs could be linked.